Artificial Intelligent Technologies and Elderly: Decoding the Stimuli towards the Artificial Intelligent Technology Adoption - Ghosh, Dr. Mun Mun (The journal of contemporary issues in business and government, 2021)
Technology has overtaken our lives, and we are bounded by the immense layers of digital and technology. It makes our lives easy-going and convenient, but it is far more complicated for those who cannot even imagine getting used to such an environment and are unfamiliar with them. Here the study gives a broad understanding of the insight of the elderly towards innovative, intelligent technologies. It also explores and explores the stimuli that motivate and encourage them to adopt AI-based advanced technologies. The study used a quantitative approach and applied Structural Equation Modelling to validate and establish the identified constructs. A total of 238 respondents were considered for the study. The findings will enable both the researchers and the practitioners to broaden their vision and acknowledge that technological innovations are possible across cohorts.